Avaliação histológica do contato osso-implante e estabilidade de implantes com superfícies modificadas : estudo experimental em tíbias de coelhos - Nunes, Leandro Soeiro de Souza (2014)
The clinical success of the implant treatment is strongly related with the achievement and maintenance of the stability of the fixture. As the surface topography, roughness and wettability are modifications that can affect the quality of the osseointegration, several studies have analyzed the benefits of these modifications. The histomorphometric analyses of the bone-to-implant contact (BIC) and the resonance frequency analyses (RFA) are commonly used to verify the osseointegration and implant stability. In the present study, 32 implants with two different surfaces treatment were installed in the tibia of 16 New Zealand rabbits and splitted in two groups. The Group I was formed by Neodent Drive implants, with sandblasted, acid etched and hydrophilic surface (Neodent Drive Acqua, Neodent, Curitiba, Brasil). The Group II was formed by Neodent Drive implants, with sandblasted and acid etched surface (Neodent Drive Porous, Neodent, Curitiba, Brasil). The samples were analyzed at 07, 14, 30 and 60 days after the implant placement. The results showed statistically significant differences between the mean values for the BIC at 14 (p=0.028) and 30 days (p=0.028). The mean BIC for the Acqua implants (Group I) were 43,32 ± 1,31% and 55,03 ± 5,14%, at 14 and 30 days respectively. The mean BIC in the Porous implants (Group II) were 46,27 ± 0,10% and 47,13 ± 0,67%, at 14 and 30 days, respectively. At 60 days, the mean BIC for the Acqua implants were 54,68 ± 3,51% and for the Porous implants were 50,86 ± 1,03%. There were not statistically significant differences in the implant stability quotient (ISQ) measurements between Acqua and Porous implants, except at 07 days after the implant placement. At day 07, the results of the present study showed higher ISQ values for the Porous implants (68,75 ± 4,16%) than Acqua implants (61,5 ± 8,01%). The follow-up ISQ analyses in the same Group, showed statistically significant increases of the mean values from 7 to 60 days and from 30 to 60 days, for both groups. In conclusion, the sandblasted and acid etched treatment used to create roughness on the Neodent implant surface is reliable and allows bone apposition, as the BIC and ISQ values found were similar or superior than the showed in the literature for similar animal models and similar implant surface. The increase of the BIC and ISQ values on the follow up showed the achievement of the secondary stability and the increase in stiffness between the implant fixture and the surrounding tissues. There were not identified better results with the hydrophilic surface during the early period of healing. Thus, further investigations are necessary to confirm the suggested results in this present study.